The Impact of Polarized Extragalactic Radio Sources on the Detection of CMB Anisotropies in Polarization - Marco Tucci; Luigi Toffolatti (Advances in Astronomy)
Recent polarimetric surveys of extragalactic radio sources (ERS) at frequencies  ν≳1 GHz are reviewed. By exploiting all the most relevant data we study the frequency dependence of polarization properties of ERS between 1.4 and 86 GHz. For flat-spectrum sources the median (mean) fractional polarization increases from 1.5% (2–2.5%) at 1.4 GHz to 2.5–3% (3–3.5%) at ν>10 GHz. Steep-spectrum sources are typically more polarized, especially at high frequencies where Faraday depolarization is less relevant. Current data suggest that at high radio frequencies (ν≥20) GHz the fractional polarization of ERS does not depend on total flux density and moderately increases with frequency. We estimate ERS number counts in polarization and the contribution of unresolved polarized ERS to angular power spectra. A first application is for the Planck satellite mission: we predict that only a dozen polarized ERS will be detected by the Planck LFI, and a few tens by the HFI. As for CMB power spectra, ERS should not be a strong contaminant to the CMB E-mode polarization at ν≳70 GHz, but they can become a relevant constraint for the detection of the cosmological B-mode polarization if the tensor-to-scalar ratio is ≲0.01.